2021
DOI: 10.1192/bjo.2021.993
|View full text |Cite
|
Sign up to set email alerts
|

Using objective clinical metrics to understand the relationship between the electronic health record and physician well-being: observational pilot study

Abstract: Background Electronic health records (EHRs) are a significant contributor to physicians’ low satisfaction, reduced engagement and increased burnout. Yet the majority of evidence around EHR and physician harms is based on self-reported screen time, which may both over- and underreport actual exposure. Aims The purpose of this study was to examine how objective EHR use correlates with physician well-being and to develop preliminary recommendations for well-being-based EHR interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Most studies were observational (91 articles) while a minority were experimental (11 articles). Nine of the observational studies examined associations between EHR use and an outcome in the cohort of observed users such as burnout, 6 , 7 , 33 , 46 , 47 , 67 , 69 turnover, 28 and stress. 71 Three observational studies examined associations between EHR use and clinical outcomes including next-day discharge, 78 length of stay, 84 and speed of consult response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were observational (91 articles) while a minority were experimental (11 articles). Nine of the observational studies examined associations between EHR use and an outcome in the cohort of observed users such as burnout, 6 , 7 , 33 , 46 , 47 , 67 , 69 turnover, 28 and stress. 71 Three observational studies examined associations between EHR use and clinical outcomes including next-day discharge, 78 length of stay, 84 and speed of consult response.…”
Section: Resultsmentioning
confidence: 99%
“… 75 , 93 , 94 , 113 Only one of the experimental studies was a randomized controlled trial. 75 Across both observational and experimental studies, 41 articles compared EHR use across different groups of users including comparisons by specialty (14 studies), 4 , 7 , 25 , 29 , 31 , 36 , 42 , 48 , 51 , 58 , 59 , 85 , 105 , 115 clinical role (12), 24 , 26 , 33 , 37 , 46 , 65 , 76 , 95 , 99 , 106 , 108 , 115 gender (8), 19 , 34 , 47 , 49 , 66 , 68 , 70 , 106 year in residency (8), 31 , 32 , 35 , 39 , 52 , 56 , 57 , 95 organization (3), 24 , 44 , 75 and country (1). 27 Vendor-measure studies were more likely than investigator-measure studies to make such comparisons of EHR use by user group (65% vs 25...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected eleven metrics of interest from the Montefiore Health Epic Signal database, consistent with prior research performed on patient volume, physician efficiency, and physician burnout. 18,[23][24][25] Using the Epic Signal web-based dashboard, we selected performance metrics displayed under 'Overview,' 'In Basket,' 'Notes and Letters,' and 'Workload' metrics as we hypothesized that these categories were most likely to be affected by the COVID-19 pandemic and resulting switch from in-person, to telehealth and hybrid models of care. Patient volume was assessed using number of appointments per day and total number of messages received per day.…”
Section: Background and Significancementioning
confidence: 99%
“…A pilot study on British physicians even suggested that more time spent on writing notes might be associated with a reduction in emotional wellbeing and engagement in work. 18 We sought to investigate the typing skills of the healthcare community in two large university hospitals in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%